The practice of collective bargaining - Beal, Edwin Fletcher; Begin, James P. (Homewood, Ill. : R.D. Irwin, 1982)
The aim of this edition is to take another step forward in the authors attempts to analyze the practice of collective bargaining in the United States. The authors viewpoints are set in perspective against developments in the theory of collective bargaining, the ongoing research of behavioral scientists, and the onward march of economic and social progress.
Includes bibliographical references and index.
rpm 19/02/2018; ijb 31/01/2019
Loans
Keywords: Collective bargaining; Grievance arbitration